Растрування кольороподілених зображень та аналіз параметрів, що впливають на чіткість в поліграфічній репродукції - Біла, Д. С. (ХНУРЕ, 2024)
Image reproduction quality, whether a photo or drawing, relies on hatching detail precision. The complex process involves rasterization, transforming halftones, and uses electronic devices. Raster shapes (round, square, chain-like, elliptical) impact clarity, contrast, and detailing. Screen ruling and dot diameter affect clarity. Moiré patterns are combated by proper raster orientation. To achieve optimal hatching detail reproduction, use high-quality originals, select suitable rasterization tech, parameters, and consult professionals. Image clarity results from various factors, demanding consideration when choosing reproduction tech and parameters.
Keywords: поліграфічна репродукція; растрування